PEO layers on Mg-based metallic glass to control hydrogen evolution rate - K. Cesarz-Andraczke; A. Kazek-Kęsik (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2020)
The amorphous Mg-based alloys may be used as metallic biomaterials for resorbable orthopedic implants. The Mg-Zn-Ca metallic glasses demonstrate variable in time degradation rate in simulated body fluid. In this work the Mg66Zn30Ca4 alloy was chosen as a substrate for coatings. This paper reports on the surface modification of a Mg66Zn30Ca4 metallic glass by plasma electrolytic oxidation (PEO). The structure characterization of uncoated Mg66Zn30Ca4 alloy was performed by using TEMand XRD method. The immersion tests of coated and uncoated Mg66Zn30Ca4 alloy were carried out in Ringer’s solutionat 37°C. The volume of released hydrogen by immersion tests was determined. The coatings structure and chemical composition after immersion tests by SEM/EDS were studied. Based on SEM images of surface structure samples, immersion tests results and hydrogen evolution measurement was proposed the course of corrosion process in Ringer’s solution for Mg-based metallic glasses with PEO coating. Results of immersion tests in Ringer’s solution allowed to determine the amount of evolved hydrogen in a function of time for Mg66Zn30Ca4 metallic glass and sample with PEO coating. In comparison to the non-coated Mg66Zn30Ca4 alloy, the sample with PEO layer showed a significantly decreased hydrogen evolution volume.